The Sense of Commitment in Individuals With Borderline Personality Traits in a Non-clinical Population - Ooi, Jinnie; Francová, Anna; Székely, Marcell; Michael, John (Frontiers in Psychiatry, 2018)
This is the first study to report evidence for the hypothesis that individuals' sense of commitment in joint activities and relationships may be influenced by personality traits characteristic of borderline personality disorder (BPD). This study consisted of 3 online experiments implemented via Amazon Mechanical Turk. Participants were presented with videos (Exp 1) or vignettes (Exp 2 and 3) describing situations in which everyday commitments were violated. Participants then reported their perceptions, interpretations, and affective and behavioral responses to those situations. Participants' BPD traits were assessed using the short form of the Five-Factor Borderline Inventory on the basis of which they were divided into two groups: High and Low BPD. The results revealed that participants with High BPD traits were less optimistic about others acting in accordance with an implicit sense of commitment (Exp 1), although there was no difference between groups when the commitment was explicitly stated (Exp 3). Participants in the High BPD group also reported heightened emotional responses (Exp 1-3) and less adaptive behavioral responses (Exp 1 and 3) to perceived or anticipated violations of commitment. Our findings suggest that high levels of BPD traits may give rise to a difficulty in adapting one’s social expectations and behavior in light of interpersonal commitments and in a manner that is calibrated to the social norms in the community. Future research should investigate to what extent a disturbed sense of commitment may contribute to the difficulties in interpersonal functioning experienced by many individuals with a clinical diagnosis of BPD.